Pengaruh Model Pembelajaran Berbasis Masalah terhadap Kemampuan Siswa dalam Menulis Teks Drama pada Siswa Kelas VIII MTS As`ad Olak Kemang Kota Jambi - Fahrozi, Fahrozi; B, Herman; Nurfadillah, Nurfadillah (Jurnal Ilmiah Dikdaya, 2024)
This research aims to determine the effect of the problem-based learning model on students' ability to write drama texts for class VIII students at MTS As'ad Olak Kemang, Jambi City. This research uses quantitative methods with experimental methods. The sampling technique for this research used class random sampling technique. The learning model used in learning is a problem-based learning model. The problem-based learning model is one of the models used in the 2013 curriculum. This learning model is student-centered. According to Albanese in Muis (2019:15) the problem-based learning model is an activity in the learning process that is able to develop students' knowledge and skills in solving a problem based on a real problem. This learning model encourages students to be more active in the learning process, so that this goal is achieved, students will be presented with a real problem to be solved, this requires thinking abilities and skills in solving a problem. Drama is a work of art, Suharianto (1982:68-69) said that drama is an art whose work is based on human life and its diversity. Using a problem-based learning model that is based on real problems to be solved will be a good way to develop students' abilities in writing drama texts.